EFEKTIVITAS METODE SAS (STRUKTUR ANALITIK SINTETIK) DALAM MENINGKATKAN KETERAMPILAN MEMBACA BAGI ANAK LAMBAT BELAJAR (SLOW LEARNER) DI SDN DEMANGAN - Lisnawati Lisnawati; Muthmainah Muthmainah (UIN Sunan Kalijaga, 2018)
Abstract. This research aims to know the effectiveness of the SAS method (Structure Analytic Synthetic) for improving the reading skills to slow learner children in SDN Demangan. The subject were 8 slow learner student, who were divided into two groups, 4 student in experimenal group and 4 student in control group. The characteristics subjects in this research was slow learner children and indicated a low reading skills. The hypothesis of this research was SAS method effective in improving reading skills for slow learner studentin SDN Demangan. This research was a pure experiment research with randomized pretest-posttest control group design or using two independent groups with pretest-postets design. Mann Whitney U and Wilcoxon were used as data analisys technique. The result of Wilcoxon analysis, between the scores of pretest and posttest in experimental group is p = 0,011 (p < 0.05). These results indicated that there was differencess between the scores before and after in reading skills of group experiments. The results of Mann Whitney U analysis between a score of posttest control group and the experimental value obtained p = 0.019 (p < 0.05). These results indicated that there was a difference reading skills between the control group and experimental group. So it can be concluded that the SAS method is effective for improving the reading skills at subjects in this research.